Edukasi Pentingnya Pengetahuan Ibu dalam Upaya Mencegah Terjadinya Stunting pada Balita di Desa Sidomulyo Kabupaten Tulungagung - Puryanti, Puryanti; Indahyati, Emilya; Hanifah, Alya Rizq (STIKES Yayasan RS.Dr.Soetomo, 2024)
Stunting is a nutritional problem that remains unresolved in Indonesia. In 2022 the stunting rate in East Java is 19.2%, for Tulungagung Regency it is currently 17.3%. This figure is still high compared to the Indonesian government's target of 14%. Many factors can cause stunting, such as maternal knowledge about stunting, nutrition, and parenting. This community service aims to educate mothers on the importance of mothers' knowledge about stunting, nutrition, and parenting in preventing stunting. The method used is material presentation, giving a pretest and posttest to measure the level of knowledge. The target of the activity is mothers who have toddlers in Sidomulyo village. The results showed that 80% of mothers who had stunted toddlers had a poor level of knowledge and 91.7% of mothers who had non-stunted toddlers had a good level of knowledge. After education shows an increase in knowledge, namely mothers who have stunting toddlers and mothers who have non-stunting toddlers have a good level of knowledge. In conclusion, there is an increase in maternal knowledge after participating in educational activities.